Development of a Lid Sealed furnace for the production of Magnesium alloys - Shaiful Rizam, Shamsudin; Azmi, Kamardin; Mohd Nazree, Derman; Shamsul Baharin, Jamaludin; Azremi, Abdullah Al Hadi; A.M.H. Firdaus; Mazlee, Mohd Noor; C.I. Mahdi; Abdul Razak, Daud; Roslinda, Shamsudin (Universiti Kebangsaan Malaysia (UKM), 2009)
Organized by Universiti Kebangsaan Malaysia (UKM), 3rd - 4th December 2008 at Danau Golf Club, Bangi, Selangor.